2015
DOI: 10.12659/msm.893415
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Nasopharyngeal Carcinoma TNM Staging with Serum EA IgA and VCA IgA in EBV and VEGF-C and -D

Abstract: BackgroundNasopharyngeal carcinoma often occurs in humans in the nasopharyngeal epithelium area. Ebstein-Barr (EB) virus plays a key role in the process of nasopharyngeal carcinoma lesions. Early antigen antibody (EA-IgA) and viral capsid antigen IgA (VCA-IgA) of EB virus detection in serum can effectively monitor the process of nasopharyngeal carcinoma lesions. Serum vascular endothelial growth factor (VEGF) -C and VEGF-D expression detection can reflect the distant metastases ability of human tumor cells.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
14
0
4
Order By: Relevance
“…With recent advances, several high‐quality, repeatable, and economical ELISA kits have been commercialized for testing serum EBV antibodies, including VCA‐IgA and EA‐IgA. Thus, the quantification of serum EBV antibodies in patients with NPC may reflect the tumor burden and provide reliable indexes for clinical TNM staging . However, to date, only two studies have evaluated the prognostic value of EBV antibodies in NPC .…”
Section: Discussionmentioning
confidence: 99%
“…With recent advances, several high‐quality, repeatable, and economical ELISA kits have been commercialized for testing serum EBV antibodies, including VCA‐IgA and EA‐IgA. Thus, the quantification of serum EBV antibodies in patients with NPC may reflect the tumor burden and provide reliable indexes for clinical TNM staging . However, to date, only two studies have evaluated the prognostic value of EBV antibodies in NPC .…”
Section: Discussionmentioning
confidence: 99%
“…[29] Activation of EBV results in a viral replication process (lytic process) when VCA and EA are expressed. [23,27] Therefore, morphological changes in epithelium such as metaplasia, insitu carcinoma and micro-invasive carcinomas that can be found in the early stages of NPC usually have not shown an increase of anti-EBV antibodies. [23] In addition, IgA levels are also influenced by the patient's immunological, racial/genetic and geographic conditions.…”
Section: Vca Antibodies To Epstein-barr Virusmentioning
confidence: 99%
“…1 It has been reported that the annual incidence of NPC in Cantonese population in China to be over 20/100000, which counts for about 78% of the head and neck malignant tumors in recent years. 1,2 NPC is relatively uncommon in the United States with about 1.6 per 100,000 diagnosed in 2015. 3 The infection of Epstein-Barr virus is thought to be the main inducing factor for NPC.…”
Section: Introductionmentioning
confidence: 99%